(untitled) - Johansson, Frans (Boston, Massachusetts, 2017)
Why do so many world-changing insights come from people with little or no related experience? Charles Darwin was a geologist when he proposed the theory of evolution. And it was an astronomer who finally explained what happened to the dinosaurs. Frans Johansson's The Medici Effect shows how breakthrough ideas most often occur when we bring concepts from one field into a new, unfamiliar territory, and offers examples how we can turn the ideas we discover into path-breaking innovations. Clayton M. Christensen--bestselling author of The Innovator's Dilemma--has described The Medici Effect as "one of the most insightful books about managing innovation I have ever read. Its assertion that breakthrough principles of creativity occur at novel intersections is an enduring principle of creativity that should guide innovators in every field." Now with a new preface and a reading guide, The Medici Effect is timeless classic that will help you reach your innovative peak.
Keywords: Đổi mới công nghệ,Technological innovations